2014
DOI: 10.1590/s1980-65742014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute static-stretching on the optimal height in drop jumps

Abstract: This study analyzed the effect of static stretching on performance during drop jumps. Furthermore, we investigated if a reduction in drop height would compensate the stretching-caused alterations. Ten physically active male subjects performed drop jumps at four different drop heights without static stretching for the optimal drop height determination. After, they performed drop jumps on two drop heights with static stretching previously. The jump height, contact time and reactive strength index were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Several researchers have argued that SS with different volumes leads to a decrease in MTS (Taniguchi et al, 2015;Pasqua et al, 2014;Akagi and Takahashi, 2013;Mizuno and Umemura, 2013;Ryan et al, 2008). Indeed, Ryan et al (2008) reported that SS of 2-8 min resulted in significant decreases in MTS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several researchers have argued that SS with different volumes leads to a decrease in MTS (Taniguchi et al, 2015;Pasqua et al, 2014;Akagi and Takahashi, 2013;Mizuno and Umemura, 2013;Ryan et al, 2008). Indeed, Ryan et al (2008) reported that SS of 2-8 min resulted in significant decreases in MTS.…”
Section: Discussionmentioning
confidence: 99%
“…RSI has been described as a simple tool to monitor stress on the MTU and to quantify plyometric or SSC performance (Werstein et al, 2012;Flanagan et al, 2008). While Pasqua et al (2014) reported that JH, GCT, and RSI were negatively influenced by a 10 min SS exercise, Tsolakis et al (2010) argued that 6 min SS exercises had no significant effects on squat jump (SJ) height, RSI, and GCT performance of well-trained fencers, either positively or negatively. Werstein and Lund (2012) also reported that SS exercises had neither a positive nor negative effect on RSI performance in female Division I soccer players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations